The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/en10060810
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Performance of Water Source Trans-Critical CO2 Heat Pump Water Heater

Abstract: Abstract:The effect of the discharge pressure on the performance of the trans-critical CO 2 heat pump with a low gas-cooler outlet temperature is experimentally investigated on a test rig of water source heat-pump water heater. The optimal discharge pressure of the trans-critical CO 2 heat pump is investigated under different external operation conditions. When the tap-water temperature is low, the characteristic of the S-shape isotherm at the supercritical region has little effect on the occurrence of the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…A multifunctional heat pump system was designed to be practical and to provide significant energy savings in building heating and hot water supply [24]. The study of a water source heat pump system showed that tap water flowrate has a negligible influence on the maximum heating capacity, while the higher water-source temperature can greatly increase the heating capacity [25]. Evan et al [26] presented a hybrid heat pump water heater (HPWH) using renewable energy and an instantaneous shower power supply control.…”
Section: Of 18mentioning
confidence: 99%
“…A multifunctional heat pump system was designed to be practical and to provide significant energy savings in building heating and hot water supply [24]. The study of a water source heat pump system showed that tap water flowrate has a negligible influence on the maximum heating capacity, while the higher water-source temperature can greatly increase the heating capacity [25]. Evan et al [26] presented a hybrid heat pump water heater (HPWH) using renewable energy and an instantaneous shower power supply control.…”
Section: Of 18mentioning
confidence: 99%
“…[10]. Su Kaynaklı Transkritik CO2 ısı pompası su ısıtıcısının performansı üzerine Liu ve ark (2017) deneysel çalışma yapmışlardır.. Musluk suyunun akış oranına ve suyun kaynak sıcaklığına pozitif şekilde bağlı olduğu söylenmiş, ek olarak musluk suyu akış oranın, maksimum ısıtma kapasitesinde önemsiz derecede etkiye sahip olduğu ve ısıtma kapasitesini büyük oranda arttırdığı belirtilmiştir [11]. CO2 Soğutkanlı transkritik soğutma çevrimlerinde Optimum Gaz Soğutucu Basıncı ve literatürdeki optimum basınç denklemlerinin karşılaştırılması Özgür (2014) tarafından incelenmiştir.…”
Section: Introductionunclassified
“…Ignacio López Paniagua et al [6] conducted a comparative study between the transcritical CO 2 HPWH and the R410A HPWH, and found that the CO 2 HPWH had better performance and broader prospects. Xiufang Liu et al [7] built a transcritical CO 2 HPWH experimental bench and found that coefficient of performance (COP) was positively correlated with water flow and water temperature.…”
Section: Introductionmentioning
confidence: 99%